2019
DOI: 10.1038/s41467-019-13313-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA REG1CP promotes tumorigenesis through an enhancer complex to recruit FANCJ helicase for REG3A transcription

Abstract: Protein products of the regenerating islet-derived (REG) gene family are important regulators of many cellular processes. Here we functionally characterise a non-protein coding product of the family, the long noncoding RNA (lncRNA) REG1CP that is transcribed from a DNA fragment at the family locus previously thought to be a pseudogene. REG1CP forms an RNA–DNA triplex with a homopurine stretch at the distal promoter of the REG3A gene, through which the DNA helicase FANCJ is tethered to the core promoter of REG3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…After discarding the supernatant, the cell pellet was resuspended in 0.5 ml PBS containing 10 μg/mL RNase A and 20 μg/mL PI stock solution and incubate at room temperature (RT) in the dark for 30 min. Cells were then subjected to analysis using a flow cytometer (FACSCanto, BD Biosciences) 70 . The gate strategy is shown in Supplementary Fig.…”
mentioning
confidence: 99%
“…After discarding the supernatant, the cell pellet was resuspended in 0.5 ml PBS containing 10 μg/mL RNase A and 20 μg/mL PI stock solution and incubate at room temperature (RT) in the dark for 30 min. Cells were then subjected to analysis using a flow cytometer (FACSCanto, BD Biosciences) 70 . The gate strategy is shown in Supplementary Fig.…”
mentioning
confidence: 99%
“…Studies have confirmed that lncRNAs can combine with different functional proteins to exhibit various effects. For instance, lncRNAs can enhance protein recruitment toward the associated target ( Chen et al, 2019 ; Yari et al, 2019 ) or can strengthen/weaken the binding force of proteins and their targets ( Liu et al, 2018 ; Wang et al, 2020 ). In this research, we demonstrated for the first time the role of GAS5 in RNA NMD of BMSCs via UPF1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a HOX transcript antisense RNA, lncRNA HOTAIR, was found to correlate with poor prognosis of lung cancer and promote tumor progression [18]. LncRNA REG1CP was shown to promote the development and progression of tumor [19]. For ESCC, several lncRNAs have been detected to associate with short survival, such as lncRNA H19 [20], lncRNA CASC9 [21] and lncRNA LUCAT1 [22].…”
Section: Introductionmentioning
confidence: 99%